PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN SWALAYAN ADA SILIWANGI SEMARANG - Ikfi Khayati, 09.05.51.0097; ., Kunartinah (Students Journal of Economic and Management, 2013)
The study entitled Effect Dimension of Quality of Service Supermarket Customer Satisfaction Siliwangi Semarang There is research to investigate and analyze whether the variables of tangible, reliability, responsiveness, assurance and empathy on the quality of services provided by the Supermarket There Siliwangi partially or jointly have an influence on customer satisfaction, the researchers took the title of